Estimates of Isotope Ratios in the Magnetosphere and Implications for Implantation of Atmosphere in Lunar Regolith - James R. Lyons; Sarah Uddin (Atmosphere, 2025)
The plasma in Earth’s magnetosphere is comprised of ions from the solar wind and from Earth’s polar wind, with the orientation of the interplanetary magnetic field (IMF) acting to modulate the relative contributions from these two sources. Although ion composition and charge state are strong indicators of ion provenance, here we consider isotope ratios as a possible additional method for tracing plasma provenance. Solar wind isotope ratios have been well characterized, but isotope ratios have not been measured for magnetospheric plasma, and only a few measurements have been made for Earth’s ionosphere. Accounting for diffusive separation in the ionosphere, and using a magnetospheric source flux model, we estimate isotope ratios for several light ions (H+, He+, N+ and O+) in the magnetosphere. The primary source of N and O magnetospheric ions is the polar wind, and He ions come primarily from the solar wind. H ions come from both polar and solar winds. The extreme diffusive separation of O+ isotopes argues against the polar wind as a significant source of O to the lunar regolith during the passage of the Moon through the magnetotail.